Phenylephrine increases tear cathepsin S secretion in healthy murine lacrimal gland acinar cells through an alternative secretory pathway. (October 2021) - Fu, Runzhong; Janga, Srikanth; Edman, Maria C.; Hamm-Alvarez, Sarah F.
Abstract: Little is known about the relationship between stimulation of lacrimal gland (LG) tear protein secretion by parasympathetic versus sympathetic nerves, particularly whether the spectrum of tear proteins evoked through each innervation pathway varies. We have previously shown that activity and abundance of cathepsin S (CTSS), a cysteine protease, is greatly increased in tears of Sjögren's syndrome (SS) patients and in tears from the male NOD mouse of autoimmune dacryoadenitis that recapitulates SS-associated dry eye disease. Beyond the increased synthesis of CTSS detected in the diseased NOD mouse LG, increased tear CTSS secretion in NOD mouse tears was recently linked to increased exocytosis from a novel endolysosomal secretory pathway. Here, we have compared secretion and trafficking of CTSS in healthy mouse LG acinar cells stimulated with either the parasympathetic acetylcholine receptor agonist, carbachol (CCh), or the sympathetic α1 -adrenergic agonist, phenylephrine (PE). In situ secretion studies show that PE significantly increases CTSS activity and protein in tears relative to CCh stimulation by 1.2-fold (***, p = 0.0009) and ∼5-fold (*, p-0.0319), respectively. A similar significant increase in CTSS activity with PE relative to CCh is observed when cultured LGAC are stimulated in vitro . CCh stimulation significantly elevates intracellular [Ca 2+ ], an effect associated with increases in the size of Rab3D-enriched vesicles consistent with compound fusion, and subsequently decreases in their intensity of labeling consistent with their exocytosis. PE stimulation induces a lower [Ca 2+ ] response and has minimal effects on Rab3D-enriched SV diameter or the intensity of Rab3D-enriched SV labeling. LG deficient in Rab3D exhibit a higher sensitivity to PE stimulation, and secrete more CTSS activity. Significant increases in the colocalization of endolysosomal vesicle markers (Lamp1, Lamp2, Rab7) with the subapical actin suggestive of fusion of endolysosomal vesicles at the apical membrane occur both with CCh and PE stimulation, but PE demonstrates increased colocalization. In conclusion, the α1 -adrenergic agonist, PE, increases CTSS secretion into tears through a pathway independent of the exocytosis of Rab3D-enriched mature SV, possibly representing an alternative endolysosomal secretory pathway. Highlights: Phenylephrine stimulates protein and fluid secretion in healthy mouse lacrimal gland in situ and in mouse lacrimal gland acinar cells in vitro . Phenylephrine increases cathepsin S secretion in mouse lacrimal gland and in acinar cell culture relative to the muscarinic agonist, carbachol. Distinct from carbachol stimulation, phenylephrine does not promote significant fusion or exocytosis of Rab3D-enriched mature secretory vesicles. Phenylephrine shows an increased ability to induce secretion from a minor endolysosomal pathway.